Characterization of the electric transport properties of black phosphorous back-gated field-effect transistors. Issue 1 (1st October 2022) - Giubileo, Filippo; Pelella, Aniello; Grillo, Alessandro; Faella, Enver; Sleziona, Stephan; Kharsah, Osamah; Schleberger, Marika; Bartolomeo, Antonio Di
Abstract: We use thin layers of exfoliated black phosphorus to realize back-gated field-effect transistors in which the Si/SiO2 substrate is exploited as gate electrode. To prevent the detrimental effect of the air exposure the devices are protected by Poly(methyl methacrylate). We report the observation of an improved contact resistance at the interface between the layered material and the metal contact by electrical conditioning. We also demonstrate the existence of a hysteresis in the transfer characteristics that improves by increasing the gate voltage sweep range. Finally, we prove the suitability of such transistors as memory devices.